Development of techniques for the isolation of a granulovirus from potato tuber moth, phthorimaea operculella (Zeller) - King, Shirley Anne (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2011)
Phthorimaea operculella, commonly known as the Potato Tuber Moth, is an economically important agricultural pest worldwide. The baculovirus, Phthorimaea operculella granulovirus (PhoGV) has been considered as a means of control alternative to chemical control because of its host specificity and harmless impact on other organisms and ecosystems. An isolate of PhoGV obtained from a South African PTM population would be beneficial in the production of a biopesticide, which is not yet available. An efficient and cost-effective rearing method would be advantageous for potential commercial production. Commercial table and seed potato plantations and storage facilities located in Patensie, Bathurst, Howick and Ivanhoe were surveyed for PTM infestations. Patensie was the only site where milky discoloured larvae were found, a potential symptom of PhoGV infection. TEM analysis revealed no virus in these samples. Since no virus was found in the field-collected samples, PTM insects were collected to initiate rearing in the laboratory. PTM was raised by three different methods in the laboratory. A cost/benefit analysis, survival rate, fertility and sex ratio were recorded for each rearing method. Rearing method one was deemed unsuccessful for efficient commercial rearing, as survival percentage and fertility were low. Rearing methods two and three had high survival rates and high fertility, and were efficient and less labour intensive than rearing method one. Rearing method three was the most productive technique, but for commercial production rearing method two was considered the most manageable and efficient. The sex ratio was 1:1 for all three cultures. The cost analysis revealed that rearing methods two and three were less expensive than rearing method one because less labour was required to monitor insects. The success of rearing PTM for 19 months will enable these cultures to be up-scaled to a large production facility for mass rearing. Virus was not found in the field surveys or in laboratory cultures, therefore chemical, temperature, humidity and carbon dioxide stressors were used in an attempt to initiate a baculoviral infection. Symptoms were exhibited in larvae subjected to chemical, temperature and humidity treatments, but these were confirmed by TEM analysis not to be a result of PhoGV infection. The success of rearing PTM in the laboratory suggests that the method could be used in the commercial rearing of the insects in a large mass-rearing facility. The data obtained from induction protocols have allowed for better understanding for future induction for PhoGV and other baculoviruses in other insect species. The failure to isolate a South African PhoGV strain for developing a biopesticide against PTM has motivated further studies in obtaining a baculovirus in order for South Africa to develop a commercial product against this pest.
Keywords: Potato tuberworm -- Larvae; Agricultural pests -- Biological control; Potato tuberworm; Baculoviruses